Pengaruh Kelas Ibu Hamil Terhadap Kecemasan Ibu Primigravida Di Puskesmas Tarabintang Kec Tarabintang Kab Humbang Hasundutan Tahun 2023 - Rosmaida Barutu; Isyos Sari Sembiring; Emma Dosriamaya Noni Br. Simanjuntak3; Ninsah Mandala Putri Sembiring; Basaria Manurung; Sonia Novita Sari (Journal Clinical Pharmacy and Pharmaceutical Science, 2023)
BACKGROUND First pregnancy for a prospective mother is a new journey marked by physical and psychological changes resulting in various psychological problems. One of the psychological aspects that influences pregnancy is anxiety. Apart from that, anxiety arises in pregnant women, influenced by the physical changes that occur during pregnancy, namely the stomach getting bigger and the body getting fatter (Utami, 2017). The pregnant women's class program in Indonesia started in 2010 and implementation at the Tarastar Community Health Center, Tarastar District, Humbang Hasundutan Regency began in 2012. One of the expected results from the implementation of the pregnant women's class is an understanding, change in attitudes and behavior of pregnant women so that pregnant women can undergo their pregnancy calmly and comfortably, avoiding physical and mental illness, and childbirth can take place normally, which ultimately contributes to reducing maternal mortality. PURPOSE: To determine the effect on anxiety of primigravida mothers at the Tarastar Community Health Center, Tarastar Subdistrict, Humbang Hasundutan Regency in 2023. The quasi-experimental design METHOD with the normality test of this data uses the Shapiro Wilk Test because it is adapted for small research samples. RESULTS: The conclusion of this study is that there is a difference in the level of anxiety between primigravida mothers who took the class for pregnant women and those who did not take the class for pregnant women. Suggestions are given for research and for research sites and for educational institutions regarding factors related to knowledge and attitudes of post partum mothers regarding Pregnancy Mother classes.